Physical activity, sedentary behaviour and their associations with cardiovascular risk in systemic lupus erythematosus. (6th November 2019) - Legge, Alexandra; Blanchard, Chris; Hanly, John G
Abstract: Objective: Using a novel isotemporal substitution paradigm, this study aimed to estimate the cross-sectional associations of objectively measured sedentary behaviour and physical activity (PA) with cardiovascular risk factors among patients with SLE. Methods: This was a cross-sectional study of adult SLE patients without documented cardiovascular disease (CVD). Cardiovascular risk factors were measured, including BMI, blood pressure, fasting glucose and lipid profile. Ten-year CVD risk was estimated using the American College of Cardiology/American Heart Association risk assessment tool. Time in sedentary behaviour, light PA, and moderate–vigorous PA (MVPA) was measured by accelerometry. We used three linear regression models—single-activity models, partition models, and isotemporal substitution models—to evaluate the associations of time spent at each movement intensity with each CVD risk variable. Results: There were 100 SLE patients [92% female; mean (s .d .) age 52.4 (14.4) years]. Only 11 participants adhered to current PA recommendations (⩾150 MVPA min/week in ⩾10-min bouts). In isotemporal substitution, reallocating 10 min from sedentary behaviour to MVPA was associated with lower systolic (β = –2.15 mmHg; P = 0.01) and diastolic blood pressure (β = –1.56 mmHg; P = 0.01), as well as lower estimated 10-year CVD risk (RR 0.81, 95% CI 0.70, 0.93). Time reallocation from light PA to MVPA was associated with lower diastolic blood pressure (β = –1.45 mmHg; P = 0.01) and lower 10-year CVD risk estimates (RR 0.80, 95% CI 0.69, 0.94). Conclusion: Given that reallocating time from other movement intensities to MVPA is associated favourably with lower cardiovascular risk, PA interventions are needed to address suboptimal MVPA levels among SLE patients.